Herbal drug technology - Agrawal, S. S. (New Delhi Universal Press, 2009)
During the past decade, there have been significant advances in herbal drug technology. In keeping with these advances, a plethora of research material on the subject has been published, but there is no authoritative textbook to guide the beginner in this vast field. This book has been designed specially to fulfil this need. Beginning with an introduction to medicinal plants and traditional systems of medicine, the book goes on to discuss medicinal botany including plant taxonomy and morphological considerations of crude drugs. It provides guidelines for setting up an in vitro culture laboratory and discusses in detail the systematic examination of crude drugs$1 (Btheir extraction and isolation. Testing of herbal drugs for effectiveness in therapy is also explained. To counteract the range of spurious drugs entering the market, standardisation of herbal drugs has been gaining importance. This book discusses the WHO protocol, different methods used for standardisation, quality control, standards for herbal extracts and validation of herbal products. The book will be useful to students and professionals in the fields of pharmacy, ayurveda, unani and siddha. Special Features: Designed according to the curriculum of undergraduate and postgraduate courses in pharmacy of various universities in India and abroad. Incorporates all recent scientific innovations and advances in a simple, lucid style. A comparative study has been made between dosage forms in ayurveda and modern medicine. Includes a detailed analysis of more than 60 phytopharmaceuticals.s
Keywords: PHARMACOGNOSY; PHARMACOGNOSY